Massive Open Online Course (MOOC) in Continuous Nursing Education (CNE): Contributions and Challenges: A Review - Aung, Khin Thandar; Mohd Ali, Noor Azizah; Musa@Mohd Zaid, Muniyati; Shaharzan, Nurul Jannah (IIUM Medical Journal Malaysia, 2022)
becomes an important aspect of the health care system and the growth in quality of health care education process. Continuous nursing education (CNE) is a lifelong professional development to enhance the knowledge, skills and attitude of nurses for the development of nursing practice, education, administration and research. The development of massive open online course (MOOC) which is an e-learning platform, has changed the approach of continuous education. However, the pedagogy in MOOC CNE is still under-developed. Although numerous roles for MOOC have been proposed in both in and out campus for nursing programs, a clear rationale for their effectiveness is still nascent. This review attempts to explore MOOC and its contributions and challenges in CNE. Literature search was conducted on articles published between 2010–2020 in Ovid MEDLINE, Embase Ovid, Ovid Emcare and CINAHL Plus databases, ScienceDirect, Web of Science, ProQuest and the Google Scholar whereby only English-language and peer-reviewed journal articles were included. Eight articles were selected for review and three aspects were extracted: i) history of MOOC, ii) characteristics of MOOC in health care, and iii) its contributions and challenges to lifelong learning as well as CNE. The findings provided valuable insights about MOOC based CNE as an inspiring approach that holds a great potential to offer credible, cost-effective and readily accessible contents to the health care providers